Framing the Rationale in Research Blogging: Establishing Relevance and Context Across Disciplines (HHH Research Blog, 2026)
ABSTRACTResearch blogging has become an important form of academic communication because it helps scholars explain not only what they study, but also why their work matters. This blog argues that framing the rationale is central to effective research blogging. A strong research blog establishes relevance, provides context, and connects with readers across disciplinary and public boundaries. Unlike journal articles, which often address specialist audiences, research blogs must speak to more diverse readers in accessible and meaningful ways. Drawing on studies of academic blogging, genre, and public communication, this discussion shows that writers need to make the problem, purpose, and significance of their work visible early in the post. It also highlights those disciplinary differences shape how rationale is presented. Overall, the blog shows that clear framing strengthens research communication and helps make scholarship more usable, visible, and engaging across different contexts.
Keywords: research blogging; rationale framing; academic communication; audience engagement; disciplinary context